(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
The manufacturing industry was traditionally considered the “modernizing” sector of the economy. However, with the growth of knowledge-intensive services and the resource-based development experiences, its role has been questioned. The article aims to identify and characterize the relationship between the income level of the countries and their productive structure, with a particular focus on manufacturing activities. A network analysis method was used to analyze a database of 57 countries at a level of 34 industries. We identified “communities” of countries grouped by the level of similarity of their productive structures. Here, we observed a strong correlation between the income level and the productive structure of countries. Then, building upon a sectoral taxonomy based the technological intensity of activities we found that high income countries, despite having undergo- ne a deindustrialization process, maintained a productive and commercial specialization –as well as in their research and development activities– in knowledge-intensive manufacturing activities. By contrast, countries with lower income levels –particularly middle-income economies–, experienced a process of deindustrialization with a relative specialization in less knowledge- intensive activities.